Comparison of N-Acetyl-L-Cysteine-Sodium Hydroxide-Based and Modified Petroff's Decontamination Method for Mycobacterium tuberculosis Culture - ARIYANI KIRANASARI; MUHAMMAD RAYHAN (Indonesian Society for microbiology, 2021)
Indonesia is one of 22 countries with a high incidence of tuberculosis in the world, particularly related to TBHIV and MDR-TB cases. Contamination of normal flora from nasopharyngeal tract is the main problem to isolate Mycobacterium tuberculosis (MTB) from sputum. Therefore, a safe solution to decontaminate sputum without killing MTB bacilli is needed. N-acetyl-L-cysteine-sodium hydroxide (NALC-NaOH)-based method and Petroff's method, which was modified with NaOH (4%) are widely used in laboratories. In the present study, we will evaluate the different of these methods. Of the 110 sputum samples were collected from suspected cases of Pulmonary TB, and the decontamination of sputum by these methods was performed, after acid-fast bacillus (AFB) smear, then the samples were cultured in Lowensteins Jensen slant medium. The positive culture was validated by chromatography test for detecting the antigen of MPT-64 and PNB. Based on the investigation, it has been shown that neither NALC-NaOH (71%) nor modified Petroff's methods (66%) had a significant effect on the positivity rate of AFB smear. However, the contamination on culture was significantly higher in samples treated with NALC-NaOH (21%) compared to Modified Petroff methods (13%) (p< 0.05). In addition, the proportion of positive culture in NALC-NaOH was lower than modified Petroff. In conclusion, our study proved that modified Petroff methods are still more effective on sputum decontamination than NALC-NaOH based on the positivity rate of MTB culture. Though, not significantly different on AFB microscopic examination.